Frederick - Lionni, Leo 1910-1999 (Dragonfly Books, 1995)
Frederick the field mouse sat on the old stone wall while his four brothers gathered food for the approaching winter days. The other mice felt that Frederick was not doing his share of the work, but when the food ran out, Frederick saved the day with what he had gathered.